The Conversion of Unicompartmental Knee Arthroplasty to Total Knee Arthroplasty with Non-CT-Based Robotic Assistance: A Novel Surgical Technique and Case Series - Raja, Hamza M.; Wesemann, Luke; Charters, Michael A.; North, W. Trevor (The Journal of Knee Surgery, 2024)
Robotic-assisted devices help provide precise component positioning in conversion of unicompartmental knee arthroplasty (UKA) to total knee arthroplasty (TKA). A few studies offer surgical techniques for computed tomography (CT) based robotic-assisted conversion of UKA to TKA; however, no studies to date detail this procedure utilizing a non-CT-based robotic-assisted device. This article introduces a novel technique employing a non-CT-based robotic-assisted device (ROSA Knee System, Zimmer Biomet, Warsaw, IN) for converting UKA to TKA with a focus on its efficacy in gap balancing. We present three patients (ages 46–66 years) who were evaluated for conversion of UKA to TKA for aseptic loosening, stress fracture, and progressive osteoarthritis. Each patient underwent robotic-assisted conversion to TKA. Postoperative assessments at 6 months revealed improved pain, function, and radiographic stability. Preoperative planning included biplanar long leg radiographs to determine the anatomic and mechanical axis of the leg. After arthrotomy with a standard medial parapatellar approach, infrared reflectors were pinned into the femur and tibia, followed by topographical mapping of the knee with the UKA in situ. The intraoperative software was utilized to evaluate flexion and extension balancing and plan bony resections. Then, the robotic arm guided placement of the femoral and tibial guide pins and the UKA components were removed. After bony resection of the distal femur and proximal tibia, the intraoperative software was used to reassess the extension gap, and plan posterior condylar resection to have the flexion gap match the extension gap. The use of a non-CT-based robotic-assisted device in conversion of UKA to TKA is a novel technique and a good option for surgeons familiar with robotic-assisted arthroplasty, resulting in excellent outcomes at 6 months.
Keywords: conversion total knee arthroplasty; unicompartmental knee arthroplasty; robotic-assisted surgery